Back-arc basin evolution in the southern Lhasa sub-terrane, southern Tibet: Constraints from U-Pb ages and in-situ Lu-Hf isotopes of detrital zircons. (November 2019) - Meng, Yuanku; Mooney, Walter D.; Ma, Yuan; Xu, Han; Tang, Rongzhen
Graphical abstract: Highlights: The Mesozoic Linbuzong Formation, part of the Gangdese region within the southern Lhasa sub-terrane, was deposited after 149 Ma. During the Late Jurassic to very Early Cretaceous, the central Lhasa sub-terrane had a relatively high relief. The central Lhasa sub-terrane was the dominant source area of the back-arc basin containing the Linbuzong Formation during the Late Jurassic to Early Cretaceous rather than the Gangdese arc. Abstract: Sedimentary rocks in the Gangdese magmatic arc document a long but poorly constrained series of tectonic events that led to basin formation. We investigate one of these events by using detrital zircon grains from Mesozoic sedimentary rocks from the Linbuzong Formation located within the Gangdese magmatic arc. Our aims are to determine the provenance of the rocks in this back-arc basin and to document the paleo-topographical uplift of the Gangdese region in southern Tibet. Detrital zircons from the Linbuzong Formation, located in the middle-eastern segment of the southern Lhasa sub-terrane, have ages in four dominant populations: 140–300 Ma, 480–700 Ma, 1000–1250 Ma, and 1400–1700 Ma. The youngest detrital zircon cluster has a weighted age of ca. 149 Ma which, in conjunction with previously published data, indicates that sedimentary rocks in the Linbuzong Formation were deposited after 149 Ma. The youngest detrital zircon grains have low 176 Hf/ 177 Hf isotopic ratios and negative εHf (t) values, similar to igneous zircons from the central Lhasa sub-terrane which is considered to be the predominant source for sediments. However, few zircon grains from the youngest age cluster have high 176 Hf/ 177 Hf ratios with significantly positive εHf (t) values, suggesting derivation of some sediments from the southern Lhasa sub-terrane, primarily the Gangdese magmatic arc. Combined with the evidence for two conspicuous age populations (480–700 Ma and 1000–1250 Ma) and the Hf isotopic characteristics of the Linbuzong Formation, we propose that the Carboniferous-Permian metasedimentary rocks from the central Lhasa sub-terrane serve as the main source of sediments for the Linbuzong Formation. We conclude that the central Lhasa sub-terrane was exhumed to the surface and attained a high relief, whereas the Gangdese magmatic arc had a relatively low relief (near sea-level) during the Late Jurassic to the Early Cretaceous.